Smart lighting system - Lim, Clarence Yue Jie (Nanyang Technological University, 2024)
With an increase in demand for energy-efficient and sustainable lighting solutions, smart lighting systems have witnessed a surge in adoption as observed by the exponential growth of the smart lighting market. Through intelligent lighting control using sensors, coupled with the integration of other systems for added functionality, grid-connected smart lighting solutions have gained traction due to the substantial energy savings and enhanced user experience that they can provide. However, while developed areas with access to the electrical grid have reaped the benefits of grid-connected smart lighting, rural regions lacking access to reliable energy sources and internet connectivity have lagged behind in the adoption of smart lighting systems. This project aims to address this disparity by developing a standalone solar-powered smart lighting system, equipped with IoT capabilities enabled by long-range wireless communication technology, that can be deployed in remote locations without access to an electrical grid.